PENGARUH PEMBELAJARAN KONTEKSTUAL TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA PADA SISWA SMA KELAS XI - Ipat, Ipat; Nindiasari, Hepsi (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2024)
This study aims to analyze the effect of contextual learning on students' conceptual understanding of mathematics in grade XI. The research employed a quantitative approach with a quasi-experimental method and a non-equivalent control group design. The sample consisted of two groups: an experimental group applying contextual learning and a control group using conventional teaching methods. The results revealed that the data were normally distributed (Shapiro-Wilk test) and homogeneous (Levene's test), making it suitable for further analysis using an independent sample t-test. The posttest mean score of the experimental group (80.47) was significantly higher than the control group (70.81), with a significance value of 0.000 (< 0.05). These findings indicate that contextual learning is more effective in improving students' conceptual understanding of mathematics than conventional methods. Therefore, contextual learning is recommended for broader implementation in mathematics education to enhance the relevance and effectiveness of learning.